Hedge Apples - Brown Recluse Spiders - and Basements - OH MY!! - Ast, Savannah; Ewing, Robert; Whitworth, Jeff (My University, 2017)
The brown recluse spider (BRS), Loxosceles reclusa (Gertsch & Mulaik) is a serious pest and not easily eradicated by chemical means (Sandidge & Hopwood, 2005). Common folklore has long indicated that Maclura pomifera (hedge apples or Osage oranges), repel spiders and insects when placed in basements (Jauron, 1997); but data is anecdotal. We collected hedge apples in in order to test whether BRS are deterred by hedge apples. Hedge apple extract appeared to ward off BRS from nesting when given a choice between nest sites that were infused or not infused.